2018
DOI: 10.3390/ma11091565
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Liquid Nitrile Rubber-Modified Epoxy Resin under Static and Dynamic Loadings: Experimental and Constitutive Analysis

Abstract: Quasi-static and dynamic compression experiments were performed to study the influence of liquid nitrile rubber (LNBR) on the mechanical properties of epoxy resin. The quasi-static experiments were conducted by an electronic universal machine under strain rates of 0.0001/s and 0.001/s, while a Split Hopkinson Pressure Bar (SHPB) system was adopted to perform the dynamic tests for strain rates up to 5600/s. The standard Zhu-Wang-Tang (ZWT) nonlinear viscoelastic model was chosen to predict the elastic behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The dynamic mechanical behavior of polymers can be described by applying the ZWT constitutive model [ 24 , 25 , 26 , 27 , 28 ]. The ZWT model is a nonlinear viscoelastic constitutive equation that can describe the mechanical properties of polymers within the range of viscoelastic deformation.…”
Section: Constitutive Modelmentioning
confidence: 99%
“…The dynamic mechanical behavior of polymers can be described by applying the ZWT constitutive model [ 24 , 25 , 26 , 27 , 28 ]. The ZWT model is a nonlinear viscoelastic constitutive equation that can describe the mechanical properties of polymers within the range of viscoelastic deformation.…”
Section: Constitutive Modelmentioning
confidence: 99%
“…This can be further extended to other Helmholtz free energy-based constitutive models such as Ogden (1984), Yeoh (1993) and eight-chain model (Bergström, 2015). More computationally inexpensive constitutive models such as the ZWT model (Xu et al, 2018) where the material Jacobian calculations are not required can also be used.…”
Section: Incorporation Of the Effects Of Stf In The Modelling Of Fabricsmentioning
confidence: 99%
“…In order to reveal the toughening mechanism of epoxy resin toughened by nano-rubber particles, the fracture toughness of the material was investigated at low (5 × 10 −4 s −1 , 1 × 10 −1 s −1 , 2.5 × 10 −1 s −1 ) and high (90 s −1 ) strain rates, and found that the toughening effect of nano-rubber particles on epoxy resin is significant at low strain rate while the toughening effect is significantly weakened at high strain rates [7]. In addition, quasi-static and dynamic compression experiments were used to reveal the effect of liquid nitrile butadiene rubber (LNBR) on the mechanical properties of epoxy resins [8], the effect of 2-Hydroxyethyl methacrylate-grafted graphene oxide (HEMA-g-GO) on the properties of photosensitive resins [9], and the effect of nanofibers on the mechanical properties of polymethyl methacrylate [10]. In order to understand the strengthening effect of structural improvement on the mechanical properties of the material, the additively-manufactured layered-hybrid lattice structure [11] and resin honeycomb structure [12,13] were selected to carry out static and dynamic mechanical properties tests, and the strain distribution was analyzed by digital image correlation (DIC) method.…”
Section: Introductionmentioning
confidence: 99%